A delayed damage model for the prediction of dynamic fracture experiments: Application on metallic structures - Suffis, Arnaud; Combescure, Alain; Chevrier, Pierre (European Journal of Computational Mechanics, 2007)
A delayed damage model was recently introduced to avoid artificial localization and mesh dependence in a softening material during a finite element analysis. This model is also interesting for transient applications because it requires only local information to predict damage and plastic strain rates. The physical idea behind this model is that the void growth rate cannot be infinite and hence the damage rate must be bounded. This paper shows that such a model does not require artificial numerical parameters and can be identified using classical spall fracture experiments. It was applied successfully to experiments performed on two aluminum alloys and one titanium alloy. The identification of the delayed damage parameters is presented. The model is applied to a simple numerical experiment which shows clearly that it avoids artificial numerical localization.